The MCP-1-2518 (A to G) single nucleotide polymorphism in Czech patients with pulmonary sarcoidosis: association with Löfgren's syndrome - Navratilova, Zdenka; Mrazek, Frantisek; Kriegova, Eva; Hutyrova, Beata; Kolek, Vitezslav; du Bois, Roland M; Petrek, Martin (Sarcoidosis, vasculitis, and diffuse lung diseases, 2007)
BACKGROUND AND AIM: The chemokine Monocyte Chemoattractant Protein (MCP)-1/CCL2, a chemoattractant for mononuclear cells, has already been implicated in the pathogenesis of sarcoidosis. A single nucleotide polymorphism (SNP) located at the position -2518 (A to G) of the MCP-1 gene has been reported to alter production of the MCP-1 protein in vitro and ex vivo. The present study, therefore, explored a possible association between MCP-1-2518 SNP and pulmonary sarcoidosis including its clinical subtypes, especially Löfgren's syndrome (LS). Relationship between MCP-1-2518 SNP and serum MCP-1 levels was also investigated. METHODS: MCP-1-2518 genotypes were determined using PCR with sequence specific primers in 105 sarcoidosis patients and 359 healthy control subjects. The differences in genotype and allelic frequencies between the patient and control groups were assessed by chi2 test. MCP-1 protein concentrations in serum samples from 77 sarcoidosis patients were determined by ELISA; Mann-Whitney U-test was used to test for differences in protein levels. RESULTS: While there was no significant difference in distribution of MCP-1-2518 alleles between sarcoidosis patients and healthy control subjects, a significantly higher proportion of the MCP-1-2518*G allele (p = 0.01, odds ratio (OR) = 2.3) and of the GG genotype (p = 0.03, OR = 3.9) was observed in the patients with LS compared to control subjects. There was also a significantly higher frequency of the MCP-1-2518*G allele in patients presenting with LS compared to the patients without LS (p = 0.04, OR = 2.1). MCP-1 protein in serum was not related to MCP-1-2518 gene variants. CONCLUSION: A possible interpretation of our results is, that the MCP-1-2518 SNP or a gene located nearby may modify clinical manifestation of sarcoidosis towards Löfgren's syndrome. Future investigations in other population(s) should, therefore, follow this case-control study.
Keywords: alely; Polymorphism, Single Nucleotide; Humans; Case-Control Studies; lidé středního věku; Sarcoidosis, Pulmonary; studie případů a kontrol; jednonukleotidový polymorfismus; Female; dospělí; Alleles; Syndrome; Genotype; lidé; chemokin CCL2; Adult; ženské pohlaví; Male; syndrom; Middle Aged; Chemokine CCL2; Genetic Predisposition to Disease; genetická predispozice k nemoci; Czech Republic; plicní sarkoidóza; genotyp; Česká republika; mužské pohlaví